Virtual Characterization of Dense Granular Flow through a Vertically Rotating Feeding Experiment. Issue 9 (28th July 2017) - Niedziela, Dariusz; Rau, Sebastian; Steiner, Konrad; de Vita, Simone; Lutsche, Marion; Richter, Meike; Schmidt, Mattias; Stoltz, Christopher
Abstract: The applicability of continuum granular flow models relies on the characterization of the macroscopic constituting relations of such models. Recent works have presented relations especially for the granular viscosity in certain well‐defined experiments. Here, a different, highly dynamic, yet dense granular flow experiment using a vertically rotating feeding device with an off‐centered rotating bottom opening together with an inverse problem approach of model essential parameters is described. For validation purposes, glass beads are used, even though the method is developed for a broader scope of materials. The same workflow is applied to a continuum and a discrete element method (DEM) model and results with a relative error in a comparable range are obtained. Abstract : Numerical simulations help to predict, analyze, and optimize the granular flow. An approach to determine material parameters in a continuum and a discrete element method model are presented. Via an inverse problem approach, a viscosity prefactor in the continuum model or friction parameters in the discrete element method model by comparing mass flow rates are established.